Improved Mathematical Problem Solving Ability and Self Efficacy of Class VIII Students of SMP Negeri 1 Percut Sei Tuan through Problem Based Learning Models - Indah Dirgantari Ritonga; Humuntal Banjarnahor; Ani Minarni (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to describe whether the increase in mathematical problem solving abilities and Self Efficacy of students who are taught using problem-based learning models is higher than students who are taught with ordinary learning, to describe whether there is an interaction between students' initial mathematical abilities and learning towards increased mathematical problem solving abilities. students, as well as to describe whether there is an interaction between students' initial mathematical abilities and learning towards increasing student Self-Efficacy. Based on the ANOVA 2 x 2 calculation, it is obtained Fcount = 88.82 while the Ftable value = 2.36 for dk (1.62) and a significant level of 5%. It turns out that the value of Fcount> Ftable, so that Ho is rejected and Ha is accepted. Then from table 4. The probability value (sig) is smaller than 0.05 so that H0 is rejected. Thus it can be concluded that the results of students' mathematical problem-solving abilities taught by problem-based learning models are better than those taught with ordinary learning models. The results of students' Self Efficacy in the problem-based learning model class were higher than in the ordinary learning model class. This can also be seen from the average results of the mathematics Self Efficacy questionnaire of students with the experimental class (99.7) which are higher than the average results of the mathematics Self Efficacy questionnaire of students with the control class (96.8). The results of students' Self Efficacy in the problem-based learning model class were higher than in the ordinary learning model class. This can also be seen from the average results of the mathematics Self Efficacy questionnaire of students with the experimental class (99.7) which are higher than the average results of the mathematics Self Efficacy questionnaire of students with the control class (96.8).X ̅=X ̅=